2017
DOI: 10.5812/semj.57573
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden of Scorpion Sting and Snake Bite from a Social Perspective in Iran

Abstract: Background: Iran is one of the countries with a high incidence of venomous animal bites, especially scorpion stings and snake bites. As a result, paying inadequate attention to education and prevention programs can impose considerable economic and social costs on the country. Thus, this study aimed to determine the economic burden of snake bite and scorpion sting through identifying direct and indirect costs imposed on the patients in the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…For wasp and bees, the cost ranged from $117 to $746,799, with an average of $20,598 ( Forrester et al, 2018 ). Another study conducted in Iran demonstrated that the cost of treatment snake bites was $ 2,104 (7,890 SR) per case, and scorpion stings cost 1192$ (4470SR) ( Mashhadi et al, 2017 ). There are additional expenses for bites and stings injuries that we are not included in this study, such as non-medical and indirect medical costs like lost earnings due to work absences, as we did not have the necessary data to calculate such cost.…”
Section: Discussionmentioning
confidence: 99%
“…For wasp and bees, the cost ranged from $117 to $746,799, with an average of $20,598 ( Forrester et al, 2018 ). Another study conducted in Iran demonstrated that the cost of treatment snake bites was $ 2,104 (7,890 SR) per case, and scorpion stings cost 1192$ (4470SR) ( Mashhadi et al, 2017 ). There are additional expenses for bites and stings injuries that we are not included in this study, such as non-medical and indirect medical costs like lost earnings due to work absences, as we did not have the necessary data to calculate such cost.…”
Section: Discussionmentioning
confidence: 99%
“…However, these numbers are still relatively low when compared to prior estimates that were made based on a literature review and a modeling study (up to 6,349 and 21,245 bites per year, respectively) [ 17 ]. In the ME, Iran (5,379), followed by Israel (322), presents the highest incidence of snakebite ( Fig 4A ) [ 18 , 21 , 138 , 139 ]. Notably, estimates suggested that up to 11,079 bites occur in Iran each year (significantly more than reported), while Israel’s estimates are lower than what is reported in the literature (155) [ 17 ].…”
Section: Animal Envenomings In the Mena Region: Country-specific Impactmentioning
confidence: 99%
“…Furthermore, these types of analyzes help politicians and decision-makers at a macro level to determine the priority of allocating funds for disease prevention and control ( 19 ). In Iran, many studies have been done to estimate the economic burden of diseases and health problems ( 20 , 21 ). For instance, costs for cases of scorpionism and snakebite were 50,656,424 $ and 11,317,416 $, respectively ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, many studies have been done to estimate the economic burden of diseases and health problems ( 20 , 21 ). For instance, costs for cases of scorpionism and snakebite were 50,656,424 $ and 11,317,416 $, respectively ( 20 ). Nevertheless, in the case of calculating the economic burden of head lice infection, no studies have been conducted in Iran.…”
Section: Discussionmentioning
confidence: 99%